O discurso sobre o uso pedagógico do desenho na Alfabetização de Jovens e Adultos (AJA) - Alcantara, Raquel Rocha Villar de (2018)
The objective of this research is to analyze the discourse about the pedagogical use of drawing in the Literacy of Youth and Adults (LYA). In methodological terms, the work moves through the Archaeological Discourse Analysis, in the Foucaultian perspective (FOUCAULT, 2008). Specifically, we aim to identify the documents that evidence this discourse; to map in the excavated documents the series of signs that constitute the statement of the pedagogical use of drawing in the LYA; describe the enunciative series that imply this discourse; and finally, to reflect on the implications of this discourse for politics and the educational practice of Literacy of Youth and Adults. Our hypothesis was the affirmation that in this discourse there are series of statements that correlate the pedagogical use of drawing in the Literacy of Youth and Adults to a problematizing education, based on the ethical, political and epistemological pillars of Popular Education. The primary corpus consisted of the CNE / CEB Opinion No. 11/2000, which deals with the National Curricular Guidelines for Youth and Adult Education; o Opinion CNE / CEB nº 23/2008 that establishes the Operational Guidelines for the Education of Youth and Adults; and finally, closing the first group of documents, the Guide of Didactic Books for the National Program of Didactic Book directed to Education of Youth and Adults. The mapping of primary documents directed us to a documentary network that allowed us to identify and analyze the discourse of "pedagogical use of drawing in LYA". After excavation, analysis and description of the statements, it was possible to identify in the enunciation of Youth and Adult Literacy two enunciative domains: the political, who mobilizes the correlate of the institutionality, giving visibility to public policies and the right to education for this public. Activating the function of militancy, evidencing the struggle for citizenship and autonomy of the people, where social movements are present in the search for the liberation of the literate subjects; the second enunciative domain is the pedagogical one, which triggers the enunciative correlate of the illiterate as a position of educating subject. On the enunciative field of pedagogical use of drawing, three domains have been identified: that of technology, which takes the architectural correlate by triggering associated fields such as geometry and mathematics; the iconic-symbolic domain, which triggers the correlate of communication and the symbolic function of drawing; finally, the pedagogical domain, with the ethical, epistemological and methodological correlates of the use of the drawing. In view of the enunciative findings, we conclude with an incursion into the pedagogical use of drawing in the Literacy of Youth and Adults and how this discourse can contribute to a problematizing education based on the ethical, political and epistemological pillars of Popular Education